Reply to commentary on the special issue Scaling up biofuels? A critical look at expectations, performance and governance. (July 2018) - Goetz, Ariane; Searchinger, Tim; Beringer, Tim; German, Laura; McKay, Ben; Oliveira, Gustavo de L.T.; Hunsberger, Carol
Abstract: The special issue Scaling up bioenergy? identifies major policy expectations attached to biofuels production worldwide, and it provides systematic reviews of actual biofuel performance and governance in these areas. Papers address the extent to which policy expectations related to climate change mitigation, energy security, rural livelihoods and risk mitigation have been achieved, and the effectiveness of public and private governance in advancing sector sustainability. Building on these findings, the synthesis paper asks, "What next?" for countries wishing to advance national biofuel programmes as one option for the necessary divestment from fossil fuels. Among other sine qua nons, the special issue highlights the urgent need to downscale global energy demand, and to stop treating biofuels as an isolated sector. Goldemberg et al. (2018) query several aspects of our approach, from research design, data collection, to our recommendation to apply the "precautionary principle" in research as well as policy making. Unfortunately, Goldemberg et al. (2018) incorrectly portray our main argument. Moreover, they claim bias in our approach and mistakes in our empirical evidence, however, without bringing forward an evenhanded critique of research philosophy, methodology or referencing different empirical literature. We fully stand behind our research philosophy and findings presented. Highlights: Emphasizes the importance of plural research approaches in energy studies. Comments on the ecological, social and economic dimensions of biofuels. Promotes the precautionary principle in advancing biofuels production and use. Emphasizes the need to scale down global demand for the sake of sustainability. Recommends context-specific strategies for sustainable production pathways.